POLA IMPLEMENTASI MANAJEMEN SUMBER DAYA MANUSIA PENDIDIKAN DALAM UPAYA MENINGKATKAN KUALITAS GURU - Putri, Agi Maehesa; Hamdiah, Neng Husnul (Jurnal Isema : Islamic Educational Management, 2023)
Indonesia's position is 67thÂ out of 209 countries in the world for the quality of education. This is still the government's main focus on efforts to improve the quality of education in Indonesia, one of which is through improving the quality of educators (teachers). The aim to be achieved through this discussion regarding Educational HRM is to be able to examine general problems related to the quality of educators that occur in educational institutions as well as the solutions offered in an effort to improve the quality of education, including (1) To analyze the flow of human resource management in educational institutions starting from planning to termination of employment, (2) To determine the implementation pattern of educational human resource management in an effort to improve teacher quality. The research carried out was research with a descriptive qualitative approach. The data collected is in the form of observations, interviews and documentation analysis and then processed using data analysis techniques in the form of data reduction, presentation and verification so that conclusion data can be obtained regarding the phenomena that occur. Educational HRM carries out its operational functions which consist of planning, recruitment and selection, placement, work performance, training and development, compensation, and termination of employment. In an effort to improve teacher quality, it must be ensured that not only operational functions are carried out, but managerial functions must also be applied in each process which includes planning, organizing, implementing and controlling. This is done on an ongoing basis so that it can be ensured that HRM education is running as it should. Based on the pattern that has been described, it is hoped that it will be able to clarify the role of the two management functions in educational HRM